Prediction of repeated hospitalizations in a psychiatric hospital for patients with paranoid schizophrenia - V. E. Pashkovskiy; A. G. Sofronov; S. A. Kolchev; E. Iu. Abritalin; I. D. Fedorovskiy; A. E. Dobrovolskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The aim of the work was to study the clinical and psychosocial characteristics of patients with paranoid schizophrenia who are under the supervision of a psycho-neurological dispensary, and to determine the predictors of the prediction rate of hospitalizations. The study examined the socio-demographic, psychosocial and clinical indicators included in a specially developed formalized map. After the correlation analysis performed using the logistic regression method, the parameters, the values of which make it possible to predict the hospitalization rate, were determined. It has been established that it is possible to assume frequent hospitalizations in patients with a severe mental state, determined by the general clinical impression scale, a history of more than 20 previous hospitalizations, the absence of a specific place of residence, the lack of communication with other people, the absence of a family, more than 4-5 appointments made to a hospital in 5 years, and the absence of a job in the last 10 years.